Exploring the Use of Paradata in Predicting Nonresponse in the Indonesian Family Life Survey. Issue 126 (April 2015) - Liew, Hui-Peng; Gardner, Sheena
To date, there is a lack of empirical analysis about their effect on survey nonresponse in most developing countries, including Indonesia. To fill this research gap, this study aims to extend previous research to explore the use of paradata in predicting survey non-participation in the 2007 Indonesian Family Life Survey (IFLS4). Findings suggest that non-response may be lowered if interviewers make an effort to contact respondents during weekday afternoons and evenings, and during the weekends. Non-response may be also be lowered if survey organizations make special efforts to maintain contact with households with dependent children, disabled or sick individuals, and multiple working adults, as well as households located in urban areas.